A Internet of Things (IoT) dalam Estuarine Ecosystem: Kajian Bibliometrik: Kajian Bibliometrik - oten, Irvan (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
This study aims to analyze and investigate scientific literature related to the application of the Internet of Things (IoT) in the context of estuarine ecosystems. Estuarine ecosystems are complex and crucial environments, often the focus of conservation and environmental management efforts. With the advancement of IoT technology, there is great potential to monitor, manage, and protect estuarine ecosystems more effectively. This research presents the results of a bibliometric study of 500 titles with the keywords Internet of Things Estuarine Ecosystem in the search system using Publish or Perish (PoP) and VOS Viewer, resulting in trends in research, main topics, and knowledge gaps that can guide researchers interested in the field of IoT. Research trends related to the keywords Internet of Things Estuarine Ecosystem are identified in 5 (five) research trend keywords: prediction, deep learning, lagoon, sensor, technology, and information, which are expected to stimulate further discussion and innovation in the application of IoT to maintain the sustainability of estuarine ecosystems. Keywords: Internet of Things (IoT), estuarine ecosystem, bibliometric study.